Tantangan dan Peluang Berwirausaha di Kalangan Mahasiswa - Jui Fivri Purba; Nur Aisyah Batubara; Rinalia Fauziah Br Manik; Syafika Syafika; Nadya Viska Harahap; Nike Ayu Angelita Sitindaon (CV. Ulil Albab Corp, 2024)
Entrepreneurship among university students presents significant potential, especially with the advancement of digital technology that allows them to start businesses with minimal capital and reach a broader market through e-commerce platforms and social media. Students possess strong creativity and adaptability, placing them in a strategic position to capitalize on business opportunities in the global era. However, despite the vast opportunities, they also face challenges such as a lack of interest, experience, business knowledge, and limited capital, which often hinder their ability to start a business. This study employs a descriptive qualitative approach to explore these opportunities and challenges, offering deeper insights into strategies that students can adopt to overcome obstacles, effectively leverage opportunities, and achieve success in their entrepreneurial endeavors.